Evidence of CNS impairment in HIV infection: clinical, neuropsychological, EEG, and MRI/MRS study. Issue 3 (1st September 1998) - Harrison, M J G; Newman, S P; Hall-Craggs, M A; Fowler, C J; Miller, R; Kendall, B E; Paley, M; Wilkinson, I; Sweeney, B; Lunn, S; Carter, S; Williams, I
Abstract : OBJECTIVES: To identify by clinical examination, EEG, MRI, and proton spectroscopy, and neuropsychological assessment the prevalence of signs of CNS involvement in patients infected with HIV, and to relate such findings to the evidence of immunosuppression. METHODS: The design was a cross sectional analysis of a cohort of male patients with infected HIV with an AIDS defining diagnosis or low CD4 count (<350), and seropositive asymptomatic subjects, both groups being followed up in a longitudinal study. Control groups consisted of seronegative subjects from the same genitourinary medicine clinics. RESULTS: This report sets out the cross sectional findings at the seventh visit in the longitudinal study. Patients with AIDS had more signs of neurological dysfunction, poorer performance on a neuropsychological test battery, were more likely to have an abnormal EEG, and to have abnormalities on MRI. They more often had cerebral atrophy, abnormal appearing white matter, , and abnormal relaxometry and spectroscopy. There was little evidence of abnormality in seropositive people who had a CD4 count >350 compared with seronegative people from a similar background. CONCLUSIONS: Detailed testing failed to disclose significant CNS impairment without immunosuppression in men infected with HIV. Findings from MRI and magnetic resonance spectroscopy (MRS) correlated with those of the neurological examination and neuropsychogical assessment. A combination of such assessments offers a simple surrogate for studies of CNS involvement in HIV disease.